Lateglacial Interstadial to mid-Holocene stratigraphy and palynology at Pepper Arden Bottoms, North Yorkshire, UK - James B. Innes; Mairead M. Rutherford; David R. Bridgland; Ben R. Gearey; Malcolm C. Lillie; Wishart A. Mitchell; Charlotte E. O'Brien; Richard T. Jones; Gareth J. Thompson (Proceedings of the Geologists' Association, 2024)

On the distinction of pollen grains of early varieties of Hordeum from Glyceria species: addressing the early cereal cultivation problem in palynology - Bruce M. Albert; James B. Innes (Palynology, 2020)

Lateglacial and Holocene relative sea‐level changes and first evidence for the Storegga tsunami in Sutherland, Scotland - Antony J. Long; Natasha L. M. Barlow; Sue Dawson; Jon Hill; James B. Innes; Catherine Kelham; Fraser D. Milne; Alastair Dawson (Journal of Quaternary Science, 2016)
We reconstruct one of the longest relative sea‐level (RSL) records in north‐west Europe from the north coast of mainland Scotland, using data collected from three sites in Loch Eriboll (Sutherland) that we combine with other studies from the region. Following deglaciation, RSL fell from a Lateglacial highstand of +6−8 m OD (Ordnance Datum = ca. mean sea level) at ca. 15 k cal a BP to below present, then rose to an early Holocene highstand and remained at ca. +1 m OD between ca. 7 and 3 k cal a BP, before falling to present. We find no evidence for significant differential Holocene glacio‐isostatic adjustment between sites on the north‐west (Lochinver, Loch Laxford), north (Loch Eriboll) and north‐east (Wick) coast of mainland Scotland. This suggests that the region was rapidly deglaciated and there was little difference in ice loads across the region. From one site at the head of Loch Eriboll we report the most westerly sedimentary evidence for the early Holocene Storegga tsunami on the Scottish mainland. The presence of the Storegga tsunami in Loch Eriboll is predicted by a tsunami wave model, which suggests that the tsunami impacted the entire north coast of Scotland and probably also the Atlantic coastline of north‐west Scotland.

Holocene and Lateglacial relative sea‐level change in north‐west England: implications for glacial isostatic adjustment models - Jeremy M. Lloyd; Yongqiang Zong; Paul Fish; James B. Innes (Journal of Quaternary Science, 2013)
Relative sea‐level (RSL) change is reconstructed for central Cumbria, UK, based on litho‐ and biostratigraphical analysis from the Lateglacial to the late Holocene. The RSL curve is constrained using ten new radiocarbon‐dated sea‐level index points in addition to published data. The sea‐level curve identifies a clear Lateglacial sea‐level highstand approximately 2.3 m OD at c. 15–17 k cal a BP followed by rapid RSL fall to below −5 m OD. RSL then rose rapidly during the early Holocene culminating in a mid‐Holocene highstand of approximately 1 m OD at c. 6 k cal a BP followed by gradual fall to the present level. These new data provide an important test for the RSL predictions from glacial isostatic adjustment models, particularly for the Lateglacial where there are very little data from the UK. The new RSL curve shows similar broad‐scale trends in RSL movement predicted by the models. However, the more recent models fail to predict the Lateglacial sea level highstand above present reconstructed by the new data presented here. Future updates to the models are needed to reduce this mismatch. This study highlights the importance for further RSL data to constrain Lateglacial sea level from sites in northern Britain. Copyright © 2012 John Wiley & Sons, Ltd.

Collisional accretion of a Late Ordovician oceanic island arc, northern Tasman Orogenic Zone, Australia - R. A. Henderson; B. M. Innes; C. L. Fergusson; A. J. Crawford; I. W. Withnall (Australian Journal of Earth Sciences, 2011)

Vegetation change during the Mesolithic and Neolithic on the Mizen Peninsula, Co. Cork, south-west Ireland - Timothy M. Mighall; Scott Timpany; Jeffery J. Blackford; Jim B. Innes; Charlotte E. O’Brien; William O’Brien; Stephan Harrison (Vegetation History and Archaeobotany, 2008)

Earliest Holocene vegetation history and island biogeography of the Isle of Man, British Isles - J. B. Innes; R. C. Chiverrell; J. J. Blackford; P. J. Davey; S. Gonzalez; M. M. Rutherford; P. R. Tomlinson (Journal of Biogeography, 2004)
Aim To present radiocarbon dated early Holocene pollen analytical data from two sites on the northern plain of the Isle of Man and to discuss the implications of the vegetation history in relation to severance of the island from the British Isles and to identify further evidence for divergent biogeographical development previously exemplified by the survival and apparent dwarfism of late glacial Megaloceros giganteus (Giant Deer). Location The Isle of Man, British Isles. Methods Pollen analysis and AMS radiocarbon dating of late glacial to early Holocene lake sequences at Pollies and Curragh‐y‐Cowle on the northern plain of the Isle of Man. Results The pollen data indicate a prolonged period of pre‐woodland vegetation after the late Glacial/Holocene transition, which lasted for most of the first post‐glacial millennium. This persistence of pre‐forest environments meant that the expansion of Betula woodland occurred later in this part of the Isle of Man than in adjacent areas of Britain and Ireland. Conclusions The Isle of Man, in the northern Irish Sea, was isolated from Britain during the late Glacial period perhaps explaining the delayed arrival of tree species. Delayed rise of the Holocene forest compared with surrounding regions probably reflects severance of the land‐bridge with Cumbria, but also could be a function of climate changes during the early Holocene and local environmental conditions. Late survival and the dwarfism of the Megaloceros giganteus (Giant Deer) fauna is another example of biogeographical divergence during the early Holocene/late Glacial of the Isle of Man. The delayed afforestation and absence of human hunters in the Manx early Holocene offers a permissive environmental context for the as yet unproven survival of Megaloceros into the early Holocene.

Allozyme and mitochondrial DNA variation in three species of oreos (Teleostei: Oreosomatidae) from Australasian waters - R. D. Ward; N.G. Elliott; P. M. Grewe; P. R. Last; P. S. Lowry; B. H. Innes; G. K. Yearsley (New Zealand Journal of Marine and Freshwater Research, 1998)
Collections of three species of oreos (smooth oreo, Pseudocyttus maculatus; black oreo, Allocyttus niger; and warty oreo, A. verrucosus ) from Australasian waters were examined for genetic variation. Allozyme heterozygosity was high in each species (25–29 loci: mean heterozygosity per locus per sample ranging from 0.100 to 0.148), but mitochondrial DNA variation was less extensive (10 six‐base restriction enzymes: nucleotide diversity ranging from 0.0012 to 0.0021). Collections of smooth oreos from Western Australia, Tasmania, and New Zealand did not permit the null hypothesis of a single stock to be confidently rejected. Black oreos from Tasmania and New Zealand were provisionally identified as separate stocks. Warty oreos from Tasmania were provisionally identified as separate from a Western Australia/New South Wales stock.

Genetic evidence for depth‐ and spatially separated stocks of the deep‐water spikey oreo in Australasian waters - N. G. Elliott; P. S. Lowry; P. M. Grewe; B. H. Innes; G. K. Yearsley; R. D. Ward (Journal of Fish Biology, 1998)
Samples of Neocyttus rhomboidalis from eight areas off southern Australia and eastern New Zealand were examined to assess the stock structure of the species. No spatial heterogeneity was detected for mitochondrial DNA variation after restriction analysis by two enzymes detecting polymorphic cut sites. Twenty mtDNA haplotypes were recorded, with an overall haplotype diversity of 0·683. Twenty‐eight allozyme loci were examined; the mean heterozygosity per locus was 13·0%. Significant sample heterogeneity was detected at three of twelve polymorphic loci: MPI*, PGM‐1 * and, most strikingly (G ST =0·43), sSOD *. Most of the sSOD * differentiation was associated with depth rather than geographical separation; sSOD * allele frequencies of shallow and deep samples being very different. It is suggested that the correlation between the sSOD * allele frequencies and depth is more likely to reflect natural selection than reproductive isolation. The spatial patterning of the MPI * and PGM‐1 * data suggest there are at least three geographic stocks of N. rhomboidalis in Australasian waters: (1) New Zealand, (2) Western Australia and South Australia, (3) west Tasmania to New South Wales and Lord Howe Rise.

Genetic population structure of southern bluefin tuna ( Thunnus maccoyii ) - P. M. Grewe; N. G. Elliott; B. H. Innes; R. D. Ward (Marine Biology, 1997)